One and multi-compartments toxico-kinetic modeling to understand metals' organotropism and fate in Gammarus fossarum. (November 2021) - Gestin, Ophélia; Lacoue-Labarthe, Thomas; Coquery, Marina; Delorme, Nicolas; Garnero, Laura; Dherret, Lysiane; Ciccia, Théo; Geffard, Olivier; Lopes, Christelle
Graphical abstract: Highlights: Cd or Hg were measured in organs of Gammarus fossarum exposed to dissolved metals. Uptake and loss kinetics parameters were assessed by Bayesian inference TK modeling. Metal fate among organs were examined through one and multi-compartiments TK models. Multi-compartments model show the key role of intestine in the ADME process of Cd. One-compartment models suggest organ independence from each other for Hg. Abstract: The use of freshwater invertebrates for biomonitoring has been increasing for several decades, but little is known about relations between external exposure concentration of metals and their biodistribution among different tissues. One and multi-compartments toxicokinetic (TK) models are powerful tools to formalize and predict how a contaminant is bioaccumulated. The aim of this study is to develop modeling approaches to improve knowledge on dynamic of accumulation and fate of Cd and Hg in gammarid's organs. Gammarids were exposed to dissolved metals (11.1 ± 1.2 µg.L −1 of Cd or 0.27 ± 0.13 µg.L −1 of Hg) before a depuration phase. At each sampling days, their organs (caeca, cephalon, intestine and remaining tissues) were separated by dissection before analyses. Results allowed us to determine that i) G. fossarum takes up Cd as efficiently as the mussel M. galloprovincialis, but eliminates it more rapidly, ii) organs which accumulate and depurate the most, in terms of concentrations, are caeca and intestine for both metals; iii) the one-compartment TK models is the most relevant for Hg, while the multi-compartments TK model allows a better fit to Cd data, demonstrating dynamic transfer of Cd among organs.